Review: A Perspective Use and Misuse of Antibiotics (Asian Journal of Pharmaceutics (AJP), 2023)
Antibiotics are the most active chemotherapeutics among drugs; they exert their therapeutic effect by antagonizingthe growth of bacteria. Since 1910 many antibiotics have been developed with different mechanisms of actionincluding: (1) Inhibition of bacteria’s cell wallsynthesis; this class of antibiotics includes vancomycin andβ-lactam antibiotics such aspenicillins, cephalosporins, and carbapenems, (2) inhibition of protein synthesisincluding tetracyclines, aminoglycosides, macrolides, and chloramphenicol, and (3) DNA synthesis inhibitorssuch as fluoroquinolones and sulfonamides that inhibit folic acid synthesis. In this chapter, we describe the threeantibiotic classes, their mechanism of action, clinical uses, side effects, and their resistance by different bacteria